A genealogia em Foucault: uma trajetória - LEMOS, Flávia Cristina Silveira (2016)
This article aims to achieve a path of genealogy as a way to write history as question / problem, according to Michel Foucault, breaking with a continuous, linear, teleological history, which sought origins and similarities between objects and attempts to establish causal relationships between the events. A history of discursive practices, power and subjectivity was the contract proposed by Foucault. The analysis of the source and emergency broke with a whole historiographical tradition which made the events memory and monuments constructed and interpreted by categories of similarity. Foucault questions this model to make history, working with new issues and problems and working with the multiplicity of scattered, rare, heterogeneous events, in clippings of series of statements in files, without searching for early origins and without utilitarian goals to be achieved.